1991
DOI: 10.1002/1097-0142(19910401)67:7<2010::aid-cncr2820670730>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Mammography and age: Are we targeting the wrong women? A community survey of women and physicians

Abstract: To determine mammography use among women with a broad range of ages, the authors surveyed women aged 30 to 74 years and physicians practicing primary care in two eastern North Carolina counties. Twenty-five percent of women in their 30s had ever had a mammogram, and 34% intended to have one in the coming year. From 45% to 52% of women in their 40s, 50s, and 60s had ever had a mammogram, and 55% to 57% intended to have one in the next year. Thirty-seven percent of women aged 70 to 74 years had ever had a mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
5

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 7 publications
5
42
0
5
Order By: Relevance
“…Previous studies have reported individual-level risk factors and census-tract socioeconomic effect on mammography use. 7,8,[22][23][24][25][26][27]29,30,[32][33][34]43 In our study, system-level barriers to mammography and heavy smoking were associated with mammography use among white and African American women. Personal-experience barriers to mammography and no physician recommendation also were independently associated with mammography screening among white women.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported individual-level risk factors and census-tract socioeconomic effect on mammography use. 7,8,[22][23][24][25][26][27]29,30,[32][33][34]43 In our study, system-level barriers to mammography and heavy smoking were associated with mammography use among white and African American women. Personal-experience barriers to mammography and no physician recommendation also were independently associated with mammography screening among white women.…”
Section: Discussionmentioning
confidence: 93%
“…Predisposing factors previously found to be associated with screening included age, 22 race/ethnicity, 23 education level, 24 marital status, and family history of breast cancer. Enabling resources associated with screening included family income, 24,25 employment status, health insurance coverage, barriers to seeing a doctor, having access to medical care when needed, 15,23,26 knowledge about breast cancer and mammography, [27][28][29] perceived barriers and benefits of mammography, [27][28][29][30][31][32] and having a physician recommend a mammogram during the past 2 years.…”
Section: Census-tract-level Factorsmentioning
confidence: 99%
“…For instance, many studies have assessed risk perception to test models that posit an association between risk perception and health behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other research assesses risk perception to detect errors and biases in risk judgments (15)(16)(17)(18), to assess the association between risk judgments and emotion (19)(20)(21)(22)(23)(24)(25), and to increase the accuracy of people's risk perceptions (11,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Even more important, participation in screening is lowest among older women. Women age 60 years or over generally are found to be less likely to ever have received mammograms and/or CBE and are less likely to have been recently screened.…”
mentioning
confidence: 99%